FEMINISATION OF SCHOOLING: UNDERSTANDING THE DETRADITIONALIZED GENDER - Belaid, Louiza; Sarnou, Hanane (My University, 2018)
The present study examines the shift of gender roles at school. It studies the extent to which detraditionalization co-exists in the educational context. It is believed that male pupils are obliged to embrace feminine features to be accepted in society. In this regard, our main issue in this work assesses whether, in the classroom, girls and boys are equally prominent and the extent to which there is a displacement of power relations. Nowadays, schools are being feminized, whereby females outnumber males. A triangulation method is employed in this enquiry: the observation, an interview and a questionnaire. 80 pupils from Mohamed Boudhiaf secondary school (47 girls and 33 boys) were selected for this study. To sum up, males are victimized by feminising cultures in which the feminine is enhanced whereas the masculine is worsened. Gender equilibrium is required at school in order for high educational outcomes to be achieved.
Keywords: gender role, detraditionalization, feminized school, gender equilibrium